Analysis of Factors Influencing Adolescent Financial Management Patterns: A Case Study of Adolescents in South Siantar, Pematangsiantar City - Cahya Adetrya; Nur Ahmadi Bi Rahmani; Atika (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the influence of financial literacy, social environment, and a consumptive lifestyle on adolescents' financial patterns. This study used a quantitative approach with a survey method involving 100 adolescents aged 20–24 years as a sample, randomly selected in South Siantar District. Data were collected through a closed-ended questionnaire with a Likert scale. The data analysis technique used multiple linear regression analysis. The results showed that financial literacy, social environment, and a consumptive lifestyle significantly influence adolescents' financial patterns. Partially, financial literacy has a positive influence, while a consumptive lifestyle has a negative influence on adolescents' financial patterns. The social environment also showed a significant influence on adolescents' financial patterns. The resulting regression model had a coefficient of determination (R²) of 0.959, indicating that 95.9% of the variation in adolescents' financial patterns can be explained by these three independent variables. The implications of this study's results indicate that to form healthy financial patterns in adolescents, it is important to improve financial literacy and create a positive social environment, as well as reduce a consumptive lifestyle.